Associations of anemia and hemoglobin with hemoglobin A1c among non‐diabetic workers in Japan. Issue 3 (3rd November 2019) - Sakamoto, Nobuaki; Hu, Huanhuan; Nanri, Akiko; Mizoue, Tetsuya; Eguchi, Masafumi; Kochi, Takeshi; Nakagawa, Tohru; Honda, Toru; Yamamoto, Shuichiro; Ogasawara, Takayuki; Sasaki, Naoko; Nishihara, Akiko; et al.
Abstract: Aims/Introduction: We examined the association between hemoglobin A1c (HbA1c) and anemia, which was categorized into three groups according to mean corpuscular volume (MCV), as well as the association between hemoglobin in the non‐anemic range and HbA1c. Materials and Methods: We used the 2016 health checkup data from 36, 422 workers without diabetes. Anemic people were divided into three groups based on MCV: <80, 80–90 and >90 fL. Non‐anemic people were divided into four groups based on their hemoglobin levels. We carried out multiple linear regression models to estimate the means and 95% confidence intervals (CIs) of HbA1c. Results: For men, 0.2% had anemia with MCV <80 fL, 0.5% had anemia with MCV 80–90 fL, 0.9% had anemia with MCV >90 fL and 98.4% had no anemia. For women, the corresponding values were 6.1, 6.4, 2.8 and 84.7%, respectively. The adjusted mean HbA1c (%) values for men with anemia with MCV <80, 80–90 and >90 fL were 5.67 (95% CI 5.60–5.74), 5.58 (95% CI 5.54–5.62) and 5.41 (95% CI 5.37–5.44), respectively. Among men without anemia, HbA1c (%) increased from 5.36 (95% CI 5.34–5.39) in those with hemoglobin ≥17.5 mg/dL to 5.45 (95% CI 5.45–5.46) in those with hemoglobin 13.0 to <14.5 mg/dL ( P for trend <0.001). The HbA1c values were higher in men with anemia with MCV <80 fL or MCV 80–90 fL, but lower in men with MCV >90 fL, compared with non‐anemic men with hemoglobin 13.0 to <14.5 mg/dL (All P  < 0.001). Similar findings were observed in women. Conclusions: We observed elevated HbA1c among anemic people with MCV <80 fL or MCV 80–90 fL, and decreased HbA1c among anemic people with MCV >90 fL, suggesting that different types of anemia might influence HbA1c differently. In addition, non‐anemic people with lower hemoglobin levels had higher HbA1c levels, suggesting that hemoglobin levels are in need of consideration when interpreting HbA1c values among non‐anemic people. Abstract : We observed elevated hemoglobin A1c (HbA1c) among anemic people with MCV <80 fL or MCV 80–90 fL, and decreased HbA1c among anemic people with MCV >90 fL, suggesting that iron deficiency anemia and non‐iron deficiency anemia might influence HbA1c differently. In addition, non‐anemic people with lower hemoglobin levels had higher HbA1c levels, suggesting that hemoglobin levels are in need of consideration when interpreting HbA1c values among non‐anemic people.